ANALISIS KEBUTUHAN PEGAWAIDI DINAS PEKERJAAN UMUM PROPINSIKALIMANTAN BARAT - Havani E.21109020, Sachril (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The problem in this study is non-permanent employees (PTT) in a proactive and innovative work less, work only based on "waiting orders from superiors" or decree, letter of assignment and so on. In addition, HR status as PTT often recruited not from professionals, but enough to meet the administrative requirements. For example, physically and mentally healthy, not to be serving, or get a recommendation from the police as people of good character (SKCK). While professional or absence of PTT in the field that suits your needs completely ignored, which in turn is less than expected. Because it is no wonder if in many government agencies most PTT looks less productive, low discipline, and work ethic is weak. This study aims to describe the planning needs temporary employees (PTT) in the Department of Public Works of West Kalimantan Province based on job analysis and workload analysis. This type of research is used by the authors in this study is descriptive qualitative, which gives an overview, explanation is objectively right about the true state of the object under study. The research found that the formation of PTT employees at the Department of Public Works of West Kalimantan Province is not one hundred percent according to educational background, there are employees who work not in accordance with the educational background they have. However, it is not absolutely have to be fulfilled for a formal education is not the sole indicator of the placement of the PTT. In addition, the level of competence of conformity to the work is in accordance with the terms of that of the PTT needs analysis. So overall formation / PTT staffing at the Department of Public Works of West Kalimantan Province is considered appropriate. Responding to the suggestion that the phenomenon exists recommended that staffing PTT strongly according to educational background and competencies required by a field of work, then the Department of Public Works of West Kalimantan Province need to coordinate with related institutions.Keywords: Analysis, Requirements, Employee Variable.